Microfilaridermia assessment of the efficacy of Ivermectin alone and Ivermectin plus Albendazole against Onchocerciasis - Mubarik, Yusif (2016)
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Philosophy In the Department of Clinical Microbiology, School of Medical Sciences, College of Health Sciences, 2015